Correlation of serum vitamin B12, folate, and magnesium levels with severity of fibrosis in non-alcoholic fatty liver disease in the medical ICU - Kartik Goel; Shailesh Kumar; Rupesh Yadav (Critical Care Innovations)
INTRODUCTION: Non-Alcoholic Fatty Liver Disease (NAFLD) has emerged as a major public health concern worldwide. Characterised by the accumulation of fat in liver cells in the absence of significant alcohol consumption, NAFLD spans a spectrum of conditions, from simple steatosis to more severe forms such as non-alcoholic steatohepatitis (NASH), which can progress to cirrhosis and liver cancer. Recent research has also highlighted the critical role of micronutrients in the development and management of NAFLD, suggesting that deficiencies or imbalances in essential vitamins and minerals may influence disease progression and response to treatment. Therefore, the objective of the study was to evaluate the correlation of serum vitamin B12, folate, and magnesium levels with the severity of fibrosis in non-alcoholic fatty liver disease in the medical ICU. MATERIALS AND METHODS: A prospective cross-sectional observational study was evaluated involving 70 patients with NAFLD diagnosis based on history, ultrasound abdomen and fulfilling inclusion criteria during the study period. The severity of liver fibrosis in patients with nonalcoholic fatty liver disease (NAFLD) was evaluated using the NAFLD Fibrosis Score. RESULTS: Patients with low vitamin B12 had a mean fibrosis score of 0.46 (SD 1.59), compared to -1.05 (SD 1.43) for those with normal Vitamin B12 levels, with a p-value of 0.009, indicating a significant difference. Patients with low folate levels had a mean fibrosis score of -0.36 (SD 1.63), while those with normal folate levels had a mean score of -1.19 (SD 1.40), with a p-value of 1x10-6. Patients with low magnesium levels had a mean fibrosis score of -0.3 (SD 1.6), while those with normal levels had a score of -1.28 (SD 1.38) (p = 0.001), suggesting a significant difference. CONCLUSIONS: The study concluded that serum levels of Vitamin B12, folate, and magnesium are all correlated with the severity of fibrosis in patients with NAFLD, with folate showing the strongest association. Folate had a significant negative correlation of -0.45 with fibrosis scores, compared to -0.34 for Vitamin B12 and -0.31 for magnesium.